UJI EFEK ANALGESIK EKSTRAK ETANOL DAUN KELOR (Moringa oleifera Lam.) PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) - Tamimi, Alyah A.P; de Queljoe, Edwin; Siampa, Jainer P. (PHARMACON, 2020)
ABSTRACTAnalgesic medicinals are medicinals that can inhibit pain. Moringa leaves (Moringa oleifera Lam.) are known to contains alkaloid and flavonoid which have analgesic effects.The purpose of this study was to determine the analgesic effects of the ethanol extract of Moringa leaves on male white rats wistar strain (Rattus norvegicus). A total of 15 rats were divided into 5 treatment groups, namely the negative control group (CMC), positive control group (paracetamol), and the group of ethanol extract of Moringa leaves with different doses of 0.1 g, 0.2 g, and 0.4 g. Rat response was observed before giving test material and after giving test material from the 30th, 60th, 90th, and 120th minutes. Data were analyzed using ANOVA then continued with LSD test. The results showed that the ethanol extract of Moringa leaves with dosages of 0.1 g, 0.2 g, and 0.4 g had an analgesic effect on male white rats wistar strain. And among these three doses the best in providing analgesic effect is a dose of 0.4 g. Keywords: Analgesic, Moringa leaf (Moringa oleifera Lam.), Rattus norvegicus. ABSTRAKObat analgesik merupakan obat yang dapat menghambat rasa nyeri. Daun kelor (Moringa oleifera Lam.) diketahui mengandung alkaloid dan flavonoid yang memiliki efek analgesik. Tujuan penelitian ini untuk mengetahui adanya efek analgesik dari ekstrak etanol daun kelor (Moringa oleifera Lam.) pada tikus putih jantan galur wistar (Rattus norvegicus). Sebanyak 15 ekor tikus dibagi 5 kelompok perlakuan, yaitu kelompok kontrol negatif, kelompok kontrol positif, dan kelompok ekstrak etanol daun kelor dengan dosis berbeda 0,1 g, 0,2 g, dan 0,4 g. Respon tikus diamati sebelum pemberian bahan uji dan setelah pemberian bahan uji dari menit ke 30, 60, 90, dan 120. Data dianalisis menggunakan ANOVA kemudian dilanjutkan uji LSD. Hasil penelitian menunjukkan bahwa ekstrak etanol daun kelor  dengan dosis 0,1 g 0,2 g, dan 0,4 g memiliki efek analgesik terhadap tikus putih jantan galur wistar. Dan diantara ketiga pemberian dosis tersebut yang paling baik dalam memberikan efek analgesik yaitu dosis 0,4 g. Kata kunci: Analgesik, Daun Kelor (Moringa oleifera Lam.), Rattus norvegicus.